Pulsed Microwave Energy Transduction of Acoustic Phonon Related Brain Injury - Hubler, Graham K.; Hoffman, Stuart W.; Andreadis, Tim D.; DePalma, Ralph G. (Frontiers in Neurology, 2020)
Pulsed microwaves above specific energy thresholds have been reported to cause brain injury in animal models. The actual physical mechanism causing brain damage is unexplained while the clinical reality of these injuries remains controversial. Here we propose mechanisms by which pulsed microwaves may injure brain tissue by transduction of microwave energy into damaging acoustic phonons in brain water. We have shown that low intensity explosive blast waves likely initiate phonon excitations in brain tissues. Brain injury in this instance occurs at nanoscale subcellular levels as predicted by physical consideration of phonon interactions in brain water content. The phonon mechanism may also explain similarities between primary non-impact blast-induced mild Traumatic Brain Injury (mTBI) and recent clinical and imaging findings of unexplained brain injuries observed in US embassy personnel possibly due to directed radiofrequency radiation. We describe experiments to elucidate mechanisms, RF frequencies and power levels by which pulsed microwaves potentially injure brain tissue. Pathological documentation of nanoscale brain blast injury has been supported experimentally using transmission electron microscopy (TEM) demonstrating nanoscale cellular damage in the absence of gross or light microscopic findings. Similar studies are required to better define pulsed microwave brain injury. Based upon existing findings, clinical diagnosis of both low intensity blast and microwave-induced brain injury likely will require diffusion tensor imaging (DTI), a specialized water based magnetic resonance imaging (MRI) technique.